Leveraging knowledge sharing and innovation culture into SMEs sustainable competitive advantage. Issue 2 (1st December 2020) - Arsawan, I Wayan Edi; Koval, Viktor; Rajiani, Ismi; Rustiarini, Ni Wayan; Supartha, Wayan Gede; Suryantini, Ni Putu Santi
Abstract : Purpose: This study aimed to examine and explain the role of knowledge sharing in shaping innovation culture to improve business performance and build sustainable competitive advantage. Most empirical research tended to be conducted in large companies, and there are limited studies on this topic in the SME sector. Thus, the study needs to re-examine whether the theories developed to understand large companies apply to SMEs. Design/methodology/approach: This quantitative study involved 259 respondents from a 59 sampling frame consisting of three levels of management of export SMEs in the Bali province of Indonesia. The questionnaire used to gather the data used a semantic differential scale, and the data were analyzed using SmartPLS software. Findings: The results showed that knowledge sharing significantly influenced innovation culture, business performance and sustainable competitive advantage. Theoretically, this research provides insight into the body of knowledge in innovation culture and business performance as a mediator variable. Research limitations/implications: Cross-sectional design limits the authors from drawing definitive generalizations, and self-reported measures used in the study increase the chances of bias. Practical implications: The study's findings could motivate managers and practitioners to place emphasis on knowledge sharing and innovation culture in the SME sector. Originality/value: The role of knowledge sharing has been focused on large companies in several countries. However, research examining the role of knowledge sharing in building an innovation culture is still rare in the SME sector, particularly in Indonesian SMEs. Therefore, research on this topic is needed because Indonesia has not only a different culture but also different business practices.